Implementation of Digital Advertising Through Shopping Promotions and Festivals: Are they Effective? - Matondang, M I; Putra, Y H (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Digital advertising in marketplace has gain more attention from Indonesian consumer for past year. The Nationwide Online Shopping Day and shopping celebrations were being the busiest days 3-5 times than in normal days. This wonder demonstrates that shopper conduct is heavily affected by limited time exercises. With the background of the increasing phenomenon of online shopping among Indonesian consumers when there is a festival or national online shopping day, this study tries to find out the percentage of digital advertising affect consumer carried out by the marketplace, how effective is the implementation of these ads in Indonesia, especially the city of Bandung using quantitative descriptive methods, samples taken by this research are consumer online shop in Bandung from past year of 2019. Result shown that the exchange esteem during these occasions was higher than the day by day normal affect by digital ads and affect intention to buy Target achievement and comparison between total costs and coverage obtained, digital advertising on special days such as national online shopping days and other discount festivals have effectively increased consumer buying interest in the city of Bandung.